[Tamás Pál 4]
road through windscreen, horse carriage, train in the station, ferry in Szántód, Balaton, child in different situation, nice clouds before storm&sunset, weekend-house, child with rocking-horse & with dog (VERY FUNNY SCENES), Christmas child with presents, Balaton in winter